The influence of biological maturation on physical and motor performance talent identification determinants of U-14 provincial girl tennis players - van den Berg, L.; Coetzee, B.; Pienaar, A. E. (Journal of Human Movement Studies, 2006)
The aim of this study was to determine the effect of biological maturation on the motor performance and physical talent Identification determinants of u-14 provincial, girl tennis players. Twenty five (25) of the top sixteen (16) provincial female players (x = 13.21+_ 0.72 years) from the Northern Gauteng and the North-West Provinces (South Africa) respectively, participated in the study. A comprehensive battery of 21 physical and motor performance tests was conducted on each subject. Subjects were asked to complete a biological maturation identification questionnaire (BMIQ) on their stage of secondary sexual characteristics development as well as on their age of menarche (Van den Berg et al, 2002). The data was analyzed by means of descriptive statistics and a Kruskal-Wallis ANOVA. The girls could be grouped into early (n = 4), average (n = 11) and late maturing girls (n = 10) according to the feedback from the BMIQ. No statistically significant differences were found in the physical and motor performance talent identification determinants of the different biological maturation groups. However, later maturing girls seemed to have an advantage at a young age in tennis, due to the result that this group attained the highest speed, speed endurance, muscle endurance, agility and cardiovascular endurance values.